Strain effects in core–shell PtCo nanoparticles: a comparison of experimental observations and computational modelling. Issue 42 (27th October 2020) - Ellaby, Tom; Varambhia, Aakash; Luo, Xiaonan; Briquet, Ludovic; Sarwar, Misbah; Ozkaya, Dogan; Thompsett, David; Nellist, Peter D.; Skylaris, Chris-Kriton
Abstract : A per layer assessment of nanoparticle strain in Pt3 Co nanoparticles via a combination of atomic resolution microscopy and computational modelling. Abstract : Strain in Pt nanoalloys induced by the secondary metal has long been suggested as a major contributor to the modification of catalytic properties. Here, we investigate strain in PtCo nanoparticles using a combination of computational modelling and microscopy experiments. We have used a combination of molecular dynamics (MD) and large-scale density functional theory (DFT) for our models, alongside experimental work using annular dark field scanning transmission electron microscopy (ADF-STEM). We have performed extensive validation of the interatomic potential against DFT using a Pt568 Co18 nanoparticle. Modelling gives access to 3 dimensional structures that can be compared to the 2D ADF-STEM images, which we use to build an understanding of nanoparticle structure and composition. Strain has been measured for PtCo and pure Pt nanoparticles, with MD annealed models compared to ADF-STEM images. Our analysis was performed on a layer by layer basis, where distinct trends between the Pt and PtCo alloy nanoparticles are observed. To our knowledge, we show for the first time a way in which detailed atomistic simulations can be used to augment and help interpret the results of ADF-STEM strain mapping experiments, which will enhance their use in characterisation towards the development of improved catalysts.